The effect of economic growth and labor force on unemployment - Lestari, Repi (Jurnal Inovasi Ekonomi, 2023)
The aim of this study was to analyze the impact of economic growth and the labor force on unemployment in Langsa City, Indonesia. Employing a quantitative approach, the study utilized secondary data spanning a ten-year observation period from 2011 to 2020. The analytical method employed was multiple linear regression analysis conducted using EViews10 software. The findings of this study reveal that economic growth has an insignificant effect on unemployment in Langsa City. Conversely, the labor force demonstrates a significant impact on unemployment within the city. Furthermore, the results of the F-test indicate that both economic growth and the labor force collectively influence unemployment in Langsa City.